(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This illustrates pathological conditions and processes refer to the abnormalities or might the disorders in the body that can affect the normal functioning. These can help in understanding a wide range of diseases and conditions, including